Inteligência de mercado para o desenvolvimento de negócio do sistema OCESP - Duarte, Lajyárea Barros (2021)
Subject: This work presents an analysis of OCESP System problem in order to structure a business intelligence area. OCESP is an entity that represents São Paulo cooperatives. Application: A survey was conducted with internal and external stakeholders to identify strengths, weaknesses, opportunities, and threats. After that, it was possible to elaborate an action plan to solve the problem identified. The plan implementation considered a new portfolio of products for the business intelligence area. Impact: The introduction of the business intelligence area allowed the internal areas of the OCESP System to obtain data and information to support daily operations and contribute to the decision-making process. Cooperatives had access to the content that knowledge-deepen in their fields. Although the OCB System operates nationwide most of the data was related to São Paulo state, however, it will be possible to replicate it, since the OCB System has national operations, the published products may contribute information to cooperatives and state units in other states. Innovation: The solutions adopted occurred in organizational, product, and process and through the strategy of jointly dealing with the themes of cooperativism and market intelligence, which is still little explored by the Brazilian cooperative system and by business literature. Complexity: The complexity was in the organization of the proposed solution to the problem presented in this work, taking into account the specificities of cooperativism and at the same time acting in the market competing with mercantile companies. Among the facilities is the support of the OCESP System in the implantation of the market intelligence nucleus and relationship with the other areas with the new structure and as for the difficulties, there is, mainly, the data culture as a challenge to be overcome. Applied Methodology: Based on the methodology for practical and applied research by Marcondes, Miguel, Franklin and Perez (2017), it was conducted surveys and interviews with employees, managers and clients of the OCESP System. Ke